2020
DOI: 10.1016/j.pcad.2020.04.008
|View full text |Cite
|
Sign up to set email alerts
|

The impact of 2019 novel coronavirus on heart injury: A Systematic review and Meta-analysis

Abstract: Journal Pre-proof J o u r n a l P r e -p r o o f Abstract Background: Evidence about COVID-19 on cardiac injury is inconsistent.Objectives: We aimed to summarize available data on severity differences in acute cardiac injury and acute cardiac injury with mortality during the COVID-19 outbreak. Methods:We performed a systematic literature search across Pubmed, Embase and pre-print from December 1, 2019 to March 27, 2020, to identify all observational studies that reported cardiac specific biomarkers (troponin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
205
2
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(243 citation statements)
references
References 19 publications
11
205
2
11
Order By: Relevance
“…Previous studies reported non-survivors present a higher proportion of various co-existing chronic illnesses in univariate analysis [4,[10][11][12]. Consistent with previous reports [10,13,14], our study indicated that COVID-19 patients with heart, liver, and kidney comorbidities had a higher risk of related organ injuries and death, compared with those without comorbidities. The cardiac, liver, and kidney complications can occur precipitously at any point during hospitalization and are increasingly being described as late complications that can occur after improvements in a patient's respiratory status.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies reported non-survivors present a higher proportion of various co-existing chronic illnesses in univariate analysis [4,[10][11][12]. Consistent with previous reports [10,13,14], our study indicated that COVID-19 patients with heart, liver, and kidney comorbidities had a higher risk of related organ injuries and death, compared with those without comorbidities. The cardiac, liver, and kidney complications can occur precipitously at any point during hospitalization and are increasingly being described as late complications that can occur after improvements in a patient's respiratory status.…”
Section: Discussionsupporting
confidence: 90%
“…It should be noted that compared to survived patients, cardiovascular disease is linked to a significantly increased risk of death in patients who have died (p < 0.001) ( Ruan et al, 2020 ). In parallel, dead cases had the higher levels of myoglobin and cardiac troponin, thus confirming relevant findings ( Li J. W. et al, 2020 ). Meanwhile, degeneration and necrosis of cardiomyocytes was found through sporadic autopsy and biopsy histopathology, and a few of monocytes, lymphocytes, and neutrophils infiltration could be seen in the cardiac myocyte ( Yao et al, 2020 ).…”
Section: Clinical Characteristics Of Severe Acute Respiratory Syndromsupporting
confidence: 82%
“…A meta‐analysis by Li et al cardiac biomarkers were significantly higher in severe cases compared to milder cases ( P < .001), this included troponin ( P < .001), CK‐MB ( P < .001) and NT‐proBNP ( P = .009) but myoglobin was not ( P = .052). Additionally, death was also higher in patients with acute cardiac injury ( P < .001) 62 …”
Section: Discussionmentioning
confidence: 98%